2021
DOI: 10.3390/biomedicines9121838
|View full text |Cite
|
Sign up to set email alerts
|

IL-20 Cytokines Are Involved in Epithelial Lesions Associated with Virus-Induced COPD Exacerbation in Mice

Abstract: (1) Background: viral infections are a frequent cause of chronic obstructive pulmonary disease (COPD) exacerbations, which are responsible for disease progression and mortality. Previous reports showed that IL-20 cytokines facilitate bacterial lung infection, but their production and their role in COPD and viral infection has not yet been investigated. (2) Methods: C57BL/6 WT and IL-20 Rb KO mice were chronically exposed to air or cigarette smoke (CS) to mimic COPD. Cytokine production, antiviral response, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These results suggest that IL-20 cytokines that are produced in higher quantity in the context of CS exposure and/or by COPD patient airways could contribute to the defective repair capacity of the airway epithelium. Moreover, we recently demonstrated that IL-20 cytokines alter the epithelial barrier in the context of virus-induced exacerbation of COPD in mice by favoring the impact of the infection on the disorganization of intercellular junction protein [29]. This suggests that blocking IL-20 signaling could represent a potential therapeutic approach for COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IL-20 cytokines that are produced in higher quantity in the context of CS exposure and/or by COPD patient airways could contribute to the defective repair capacity of the airway epithelium. Moreover, we recently demonstrated that IL-20 cytokines alter the epithelial barrier in the context of virus-induced exacerbation of COPD in mice by favoring the impact of the infection on the disorganization of intercellular junction protein [29]. This suggests that blocking IL-20 signaling could represent a potential therapeutic approach for COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of smoke particulates is estimated to be 350 mg/cubic meter as mentioned by the manufacturer as previously described ( 32 , 33 ). Our cigarette smoke exposure models are based on classical experimental models used to analyse the mechanism of CS-induced inflammation and/or COPD in mice ( 43 , 44 ). These smoke exposure models mimic important features observed in human including epithelial injury and pulmonary inflammation with neutrophils influx ( 1 , 2 , 6 ).…”
Section: Methodsmentioning
confidence: 99%